2013
DOI: 10.1161/strokeaha.111.000598
|View full text |Cite
|
Sign up to set email alerts
|

Novel Risk Score to Predict Pneumonia After Acute Ischemic Stroke

Abstract: Background and Purpose— To develop and validate a risk score (acute ischemic stroke-associated pneumonia score [AIS-APS]) for predicting in-hospital stroke-associated pneumonia (SAP) after AIS. Methods— The AIS-APS was developed based on the China National Stroke Registry, in which eligible patients were randomly classified into derivation (60%) and internal validation cohort (40%). External validation was performed using the prospective Chinese Intracr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
172
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(193 citation statements)
references
References 45 publications
(36 reference statements)
15
172
3
3
Order By: Relevance
“…Findings of the study showed that smoking, alcohol intake, dysphagia, age, hemorrhagic type of stroke, and need for intubation were factors independently increased the risk for developing pneumonia. Age, dysphagia, hemorrhagic stroke, and need for intubation have all been previously reported as risk factors for stroke-associated pneumonia, [1,4,5,[9][10][11][12][13] which is consistent with our findings. However, this study identified another risk factor not yet reported in literature which is alcohol intake, but the data on the amount and duration of alcohol intake were not obtained.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings of the study showed that smoking, alcohol intake, dysphagia, age, hemorrhagic type of stroke, and need for intubation were factors independently increased the risk for developing pneumonia. Age, dysphagia, hemorrhagic stroke, and need for intubation have all been previously reported as risk factors for stroke-associated pneumonia, [1,4,5,[9][10][11][12][13] which is consistent with our findings. However, this study identified another risk factor not yet reported in literature which is alcohol intake, but the data on the amount and duration of alcohol intake were not obtained.…”
Section: Discussionsupporting
confidence: 93%
“…[1,6,9,13] In this study, the mean NIHSS for the cases is 19, while that for the controls is 11 with an overlap in the NIHSS scores between the two groups, suggesting statistically non-significant OR. Clinically, stroke severity can be classified using NIHSS scores as to mild (≤4), moderate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and severe (more than 15). Based on the mean scores, this study suggests that NIHSS scores differed in both groups clinically but did not attain statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Ruijun et al 22 showed that age, atrial fibrillation, congestive heart failure, chronic obstructive pulmonary disease and current smoking, prestroke dependence, dysphagia, admission NIHSS and GCS scores, stroke subtype and blood glucose were independent predictors of pneumonia in ischemic stroke. Finlayson et al 23 indicated that male sex, nonlacunar ischemic stroke, and preadmission dependency were predictors too.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying swallowing impairments, implementing dietary modification, head elevation, and shortened use of mechanical ventilation have been emphasized [32] [33]. Other investigators have developed tools for identifying patients at high risk for SAP, although it is unclear how this informs patient care at present [34] [35]. Our finding showed that hyperglycemia especially hyperglycemia with normal HgbA1C level were an independent risk factor for SAP in acute phase of ICH.…”
Section: Discussionmentioning
confidence: 76%
“…Hyperglycemia on admission is a well-known predictor of poor outcome in patients with ICH [11] [12]. Recently, there are few small studies have examined the relationship between blood glucose levels and post-stroke infection [13] [14]. No larger studies have examined the incidence of SAP or their impact on outcome in a pure ICH cohort.…”
Section: Introductionmentioning
confidence: 99%